Medical countermeasures for the hematopoietic-subsyndrome of acute radiation syndrome in space. (November 2022) - Kernagis, Dawn N.; Balcer-Kubiczek, Elizabeth; Bazyar, Soha; Orschell, Christie M.; Jackson, Isabel L.
Abstract: More than 50 years after the Apollo missions ended, the National Aeronautical and Space Administration (NASA) and other international space agencies are preparing a return to the moon as a step towards deep space exploration. At doses ranging from a fraction of a Gray (Gy) to a few Gy, crew will be at risk for developing bone marrow failure associated with the hematopoietic subsyndrome of acute radiation syndrome (H-ARS) requiring pharmacological intervention to reduce risk to life and mission completion. Four medical countermeasures (MCM) in the colony stimulating factor class of drugs are now approved for treatment of myelosuppression associated with ARS. When taken in conjunction with antibiotics, fluids, antidiarrheals, antiemetics, antipyretics, and other treatments for symptomatic illness, the likelihood for recovery and mission completion can be greatly improved. The current review describes the performance and health risks of deep space flight, ionizing radiation exposure during crewed missions to the moon and Mars, and U.S. Food and Drug Administration (FDA)-approved medical interventions to treat ARS. With an expansion of human exploration missions beyond low Earth orbit (LEO), including near-term Lunar and future Mars missions, inclusion of MCMs to counteract ARS in the spaceflight kit will be critical for preserving crew health and performance.